The Effect of Principal’s Managerial Competence and Teacher Work Culture on Teacher Competence at Junior High Schools in Cilacap - Maman Herman; Siti Andiriah; Asep Budi Tauhid (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to determine: 1) the effect of the principal's managerial ability on teacher competence; 2) The influence of teacher work culture on teacher competence; 3) The influence of the principal's managerial ability and teacher's work culture on teacher competence. This research was descriptive with a quantitative approach. The data were collected by distributing questionnaires to 71 respondents—statistical data processing using SPSS 17.0. The study results that: 1) The managerial ability of principals at Junior High Schools in Central Cilacap Subdistrict was generally in the answer always with quite high criteria. The hypothesis test results indicate that the principal's managerial ability positively affects teacher competence. It means that the higher the managerial ability of the principal, the greater the teacher’s competence; 2) The work culture of teachers in junior high schools in the Central Cilacap sub-district, in general, is in the frequent answers with quite high criteria. The hypothesis test results show that the teacher's work culture positively affects teacher competence. One means that the higher the teacher's work culture, the higher the teacher's competence; 3) The competence of teachers in junior high schools in Central Cilacap Subistrict is generally in the answer always with quite high criteria. The results of hypothesis testing indicate that the principal's managerial ability and teacher work culture positively affect teacher competence. It means that the higher the principal's managerial ability and the higher the teacher's work culture, the higher its competence.